Komparasi Kinerja Keuangan Perusahaan Food And Beverages Kategori Saham Syariah Sebelum dan pada Masa Covid-19 serta Dampaknya terhadap Harga Saham - Nurul Aisah; Triyani; Vella Diah Ayu Norisma (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
The aim of this research is to determine differences in company financial performance before Covid-19 and during Covid-19 and their impact on stock prices. This type of research uses a quantitative approach. The data analysis used in this study was a different test, namely the Wilcoxon test and panel data regression with Eviews software. The sampling method used in this study was purposive sampling. The population in this study are food and beverage sector companies in 2018-2021. The data used in this study is the annual financial reports of 11 companies in the food and beverage sector in the sharia stock category in 2018-2021 as many as 44 data. The results of data analysis show that the different test with the Wilcoxon Test results are the variables of Stock Price, ROA, Current Ratio, DER, TATO there is no difference between before and during Covid-19. And based on the selection of the model that has been done, the Fixed Effect Model is chosen to be the best model for estimating. The hypothesis test shows that the ROA variable is significant and has a positive effect on stock prices, Current Ratio is significant and has a negative effect on stock prices, while the DER and TATO variables are not significant and have no effect on stock prices. The limitations of this study only use research objects that are only focused on food and beverage companies and this research only conducts studies related to financial performance with ratios of ROA, Current Ratio, DER and TATO. Suggestions for further research are to conduct research with different objects and add other variables related to financial performance.